Penentuan Harga Pokok Produksi Usaha Mikro, Kecil, dan Menengah Charu Dhatri Madiun - Wildanul Isnaini; Halwa Annisa Khoiri; Putri Cahyaningtyas (Universitas Muhammadiyah Yogyakarta, 2022)
Micro, Small and Medium Enterprises (MSMEs) Charu Dhatri explained that there were difficulties in formulating the Cost of Production (HPP) because there were on-off workers who depended on the volume of orders. The number of workers is determined by fluctuations in orders. Therefore, workers’ wages are difficult to include in the calculation of HPP. In response, community service activities were carried out to overcome it. The solution offered to solve the partner’s problems was by providing training and assistance in calculating the cost of production (HPP). The results show that MSME production activities can run smoothly according to the plan, while partners actively participate in activities, and there is an increase in knowledge of 26.19% after training and mentoring. After that, the partner’s satisfaction through the programs and activities reached a very good level. The next hope is that Charu Dhatri’s MSME business activities will run well, healthy, and sustainably.